Transformasi Madrasah dalam Menghadapi Tantangan di Era Society 5.0 - Reza Bagus Anugerah (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2023)
This research aims to describe the transformation of madrasah in facing challenges in the era of Society 5.0. The research method employed is a literature review with primary data sourced from books on education in the era of Society 5.0, supported by secondary data. Data collection is conducted through documentation techniques by gathering data sources from various literature such as books, journals, proceedings, and valid scientific works. Data analysis adopts a qualitative approach involving data reduction, data presentation, and conclusion drawing. The research findings indicate that madrasahs in the Society 5.0 era encounter challenges in technology integration, digital literacy, curriculum updates, and teacher qualifications. The solution to facing Society 5.0 involves transforming educational technology in madrasahs, including integrating technology into learning, enhancing digital literacy, updating the curriculum with a focus on technological skills, and providing teacher training in digital teaching methods to improve qualifications and competencies. This transformation is key to ensuring the relevance and adaptability of madrasahs amidst societal and technological changes